Species richness of Antbirds (Thamnophilidae) in more central and peripheral sites of terra firme forest in the eastern edge of the Amazonia - Martínez, Carlos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Antbirds (Thamnophilidae) comprise many insectivorous, mostly understory birds present in all Neotropical biomas. Many species occur specifically in the Amazonia, so a decline in species richness is expected from central Amazonian sites, to peripheral ones; this pattern is due primarily to the evolutionary history of the taxon. Rapid surveys to state the antbird species richness were performed in six sites of terra firme forest in the Belém Center of Endemism, the Easternmost and one of the most threatened regions in the Amazonia. These sites followed a series from more central to more peripheral areas, the latter being located in the edge of the Amazonia. The antbird species richness of every site was stated by presence-absence criteria. Two surveys were made in each site, by walking three transects in each of two trails in every survey. This species richness progressively fell from 19 species in the most central site (Gurupi Biological Reserve) to only two in the most peripheral one (São Luís). Probably, the gradient in the species richness is primarily associated to the evolutionary history of this group, however new studies using methods appropriated to assess the effects of environmental degradation in the regional richness of Thamnophilidae and other forest bird species should be encouraged.